2013
DOI: 10.3171/2012.10.jns12305
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of Chiari malformation with and without syringomyelia: experience with 177 adult patients

Abstract: Surgical decompression of the posterior fossa should aim to create relatively large subarachnoid cisterns and reduce the size of the syrinx cavity. Reduction of the cerebellar tonsils by surgical means, together with duraplasty, achieves this goal and thereby improves the clinical outcome for patients with CM. An incidental observation of the study is that obesity increases the likelihood of headache in patients with CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
91
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 32 publications
6
91
1
3
Order By: Relevance
“…Batzdorf et al 9 found that the mean BMI for 177 adult patients who underwent CM-I decompression at their institution was 26.4 kg/m 2 . Similarly, Arnautovic et al 4 reported on 60 adults who underwent CM-I decompression, and they found a mean BMI of 30.4 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Batzdorf et al 9 found that the mean BMI for 177 adult patients who underwent CM-I decompression at their institution was 26.4 kg/m 2 . Similarly, Arnautovic et al 4 reported on 60 adults who underwent CM-I decompression, and they found a mean BMI of 30.4 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…3,12,19,26,28 A relatively small percentage of our patients with CM-I were symptomatic, which is consistent with previous reports of different cohorts from our institution. 26,28 Batzdorf et al 9 recently reported BMI data for 106 adult patients with CM-I who were all treated surgically. In that group, the authors found that an elevated BMI was associated with an increased likelihood of exertional headache, a symptom that was present in a majority of their patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations